Imiglucerase in the treatment of Gaucher disease: a history and perspective - Deegan, Patrick B (Dove Medical Press, 2012)
The scientific and therapeutic development of imiglucerase (Cerezyme(®)) by the Genzyme Corporation is a paradigm case for a critical examination of current trends in biotechnology. In this article the authors argue that contemporary interest in treatments for rare diseases by major pharmaceutical companies stems in large part from an exception among rarities: the astonishing commercial success of Cerezyme. The fortunes of the Genzyme Corporation, latterly acquired by global giant Sanofi SA, were founded on the evolution of a blockbuster therapy for a single but, as it turns out, propitious ultra-orphan disorder: Gaucher disease.